The complete mitochondrial genome of Thyridosmylus trimaculatus Wang, Du et Liu, 2008 (Neuroptera: Osmylidae: Spilosmylinae) with phylogenetic analysis - Ruyue Zhang; Shuo Tian; Xingyue Liu; Yuyu Wang (Mitochondrial DNA. Part B. Resources)
The complete mitochondrial genome of Thyridosmylus trimaculatus Wang, Du et Liu, 2008 with 16,011 bp long is reported here. It contains 37 annotated genes and the control region. Most protein-coding genes (PCGs) started with typical ATN, except ND1 initiated with TTG. Most PCGs terminated with the complete stop codons (i.e. TAA and TAG), while COX2, ND4, ND5, CytB terminated with T-tRNA, and ND2, ND3 terminated with TA-tRNA. Phylogenetic analysis revealed that T. trimaculatus were closely related to T. langii. Osmylinae were recovered as the sister group to Spilosmylinae + Protosmylinae. Osmylidae were demonstrated being the sister group to Nevrorthidae + Sisyridae.